Heidegger's Understanding of Hermeneutics Facticity and his Contribution to Caputo's Cold Hermeneutics in his Work entitled Radical Hermeneutics - Anam, Rifqi Khairul (Media: Jurnal Filsafat dan Teologi, 2025)
Current scholarship on Heidegger's hermeneutics of facticity often concentrates on its relationship to his broader ontology, such as Sheehan's examination of Ereignis as the "appropriated clearing" of existence, or its implications for postmodern thought, as seen in Wiercinski's exploration of hermeneutic truth and the absence of objective truth. Nevertheless, the significant connection between Heidegger's hermeneutics of facticity and its impact on Caputo's "cold hermeneutics" remains insufficiently explored. This study aims to address this gap by asserting that Heidegger's conception of facticity as the "thrownness" of Dasein into a world of pre-understandings is essential to Caputo's "cold hermeneutics," which embraces the constraints and uncertainties of interpretation. This relationship is established through the notion of Ereignis as the dynamic unfolding of facticity, enabling Dasein to appropriate its thrownness. By utilizing a methodology of "hermeneutic situation" and "formal indication," this research examines Heidegger's primary works, including Being and Time and Ontology – The Hermeneutics of Facticity, to illustrate how facticity shapes our comprehension of Being and influences the ethical and political aspects of interpretation in Caputo's writings.